Why are most colorectal cancers diagnosed outside of screening? A retrospective analysis of data from the English bowel screening programme. (December 2022) - Kerrison, Robert Stephen; Prentice, Andrew; Marshall, Sarah; von Wagner, Christian
Objective: Despite several interventions to increase participation in England, most colorectal cancers (CRCs) are diagnosed outside of the screening programme. The aims of this study were to better understand why most CRCs are diagnosed externally, the extent to which this is due to suboptimal uptake of screening, and the extent to which it is due to other factors, such as false-negative test results. Setting / Methods: We performed a clinical audit of 1011 patients diagnosed with CRC at St Mark's Hospital (Harrow, UK) between January 2017 and December 2020. Data on the diagnostic pathway and screening history of individuals were extracted from the bowel cancer screening system and assessed using descriptive statistics. Results: 446/1011 (44.1%) patients diagnosed with CRC were eligible for screening at the time of diagnosis. Of these, only 115/446 (25.8%) were diagnosed through screening. Among those diagnosed via non-screening pathways, 210/331 (63.4%) had never taken part in screening, 31/331 (9.4%) had taken part but were not up to date, and 89/331 (26.9%) had taken part and were up-to-date (of these, 82/89 [92.2%] had received a normal or weak positive test result, and 5/89 [5.6%] had received a positive result and declined colonoscopy). Conclusion: Nearly two-thirds of screening eligible patients diagnosed through a non-screening pathway had never taken part in screening. This represents the single largest source of inefficiency within the screening programme, followed by missed findings and inconsistent participation. Given the improved outcomes associated with screen-detected cancers, there is a strong public health mandate to encourage participation.